weighing words and tearing up hegemonies: self-care and failure in two fat dance pieces (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This text starts off by the aesthetic proposals of the solo pieces: Gross Weight (2016) and Essay on rhetoric(2017). In order to invest theoretically and radically in the negativity of the weight, the authors tear up the imperative of lightness in the consumer society, contrasting it through the notion of failure. Thus, the need for a cure is questioned once the protocol of illness is perceived, in which fatness is prevented from being understood beyond pathology, ugliness and laziness.
Keywords: Fatness; Failure; Self-care; Dance; Dramaturgy